Classification and treatment of prostatitis: a review of literature - Almugbel, Saad Khalid; Alanezi, Fahad Khalaf Bakit; Alhoshan, Faisal Musaad; Alkhalifa, Rayan Osama; Alkhzaim, Ali Hasan; Almohideb, Malik Abdulrahman (International Journal Of Community Medicine And Public Health, 2018)
Prostatitis is one of the most common urinary tract diseases in men of all ages and is often challenging to manage. They can be classified based of the course of illness, presentation, and their etiology, and the investigation and treatment depend on how type of prostatitis. In this study we aim to look through the literature to find the various types of prostatitis and understand the respective methods of management. We did a systematic search for prostatitis using PubMed search engine (http://www.ncbi.nlm.nih.gov/) and Google Scholar search engine (https://scholar. google.com). The terms used in the search were: prostatitis, urinary tract diseases in men, classification of prostatitis, management of prostatitis. Prostatitis is a common disease and is considered to be the third most common urological disease in men. It has been categorized into four groups: acute bacterial prostatitis, chronic bacterial prostatitis, chronic prostatitis/chronic pelvic pain syndrome, and asymptomatic inflammatory prostatitis. Treatment can be challenging, but mainly consists of use of fluoroquinolones.